2010
DOI: 10.1039/b912338e
|View full text |Cite
|
Sign up to set email alerts
|

Ferritin protein imaging and detection by magnetic force microscopy

Abstract: Magnetic force microscopy was used to image and detect ferritin proteins and the strength of the magnetic signal is discussed, revealing a large workable lift height between the magnetic tip and the ferritin sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
25
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 22 publications
8
25
1
Order By: Relevance
“…Really, the main contribution to the uncertainty in MFM quantitative analysis results from that in the magnetic properties of the tip. Therefore, although in recent years MFM has been used to quantitatively study the magnetic properties of ferritin and nanometer sized MNPs, 29 , 39 , 41 , 42 in order to definitely assess the magnetic properties of magnetoferritin and other molecules at the nanoscale the value of m ct should be calibrated using a reference sample. Recently, an approach has been proposed in which such a calibration is performed for a fixed value of Δ z using MNPs with traceably determined magnetization dispersed on a Si surface as a MFM reference sample 30 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Really, the main contribution to the uncertainty in MFM quantitative analysis results from that in the magnetic properties of the tip. Therefore, although in recent years MFM has been used to quantitatively study the magnetic properties of ferritin and nanometer sized MNPs, 29 , 39 , 41 , 42 in order to definitely assess the magnetic properties of magnetoferritin and other molecules at the nanoscale the value of m ct should be calibrated using a reference sample. Recently, an approach has been proposed in which such a calibration is performed for a fixed value of Δ z using MNPs with traceably determined magnetization dispersed on a Si surface as a MFM reference sample 30 .…”
Section: Resultsmentioning
confidence: 99%
“…Hsieh et al 39 have recently used MFM to visualize ferritin molecules, to detect their iron oxide core and to quantitatively evaluate the corresponding magnetic moment. Martinez et al 40 employed MFM to confirm the magnetic properties of iron oxide core of patterned ferritin molecules after reducing its size from 8 to 2 nm by O 2 plasma etching.…”
Section: A Short Review Of Applicationsmentioning
confidence: 99%
“…Also, plasma patterning has been used to modify PDMS surfaces to create patterned oxidized regions that exhibit hydrophilic character and can be used for cell patterning [24]. In our published work in this area, plasma patterned PDMS surfaces were used to fix ferritin proteins [25]. In this study, plasma patterned PDMS surfaces were used as an adherent substrate to provide a model system for studying the cellular motion of HCC cells with different histological grades.…”
Section: Introductionmentioning
confidence: 98%
“…MFM study of the surface of SPION nanocomposites showed that the distribution of SPIONs in a matrix can create domains in the nanocomposite . The high potential of MFM for biological and medical applications has been shown, for example, by visualization the iron core of ferritin as well as by studying the cellular uptake of SPIONs . Wang et al mapped the uptake of SPIONs into tumor cells and determined the intracellular iron content and spatial distribution of the intracellular iron .…”
Section: Introductionmentioning
confidence: 99%
“…[22] The high potential of MFM for biological and medical applications has been shown, for example, by visualization the iron core of ferritin as well as by studying the cellular uptake of SPIONs. [13,14,[23][24][25][26][27] Wang et al mapped the uptake of SPIONs into tumor cells and determined the intracellular iron content and spatial distribution of the intracellular iron. [26] Passeri et al investigated the use of superparamagnetic core shell nanoparticles for cell labeling in vitro.…”
Section: Introductionmentioning
confidence: 99%